1992
DOI: 10.1007/bf01919147
|View full text |Cite
|
Sign up to set email alerts
|

The presence of free D-serine, D-alanine and D-proline in human plasma

Abstract: Twelve neutral free amino acids, i.e. serine, threonine, glutamine, asparagine, alanine, proline, methionine, tyrosine, valine, leucine, isoleucine and phenylalanine, were surveyed for the presence of D-enantiomers in plasma samples from patients with renal diseases and from normal subjects. D-serine, D-alanine and D-proline were found in the patient's plasma. The highest concentrations (D/L ratio) of D-serine, D-alanine and D-proline were 0.2362, 0.2087 and 0.0986, respectively. The sum of the contents of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 14 publications
2
79
0
Order By: Relevance
“…In addition, D-amino acids are synthesized in vivo by microorganisms by transformation of L-isomers, which are enzymatically catalyzed by amino-acid oxidases, transaminases and racemases (Friedman, 1999). The concentration of D-proline in the human plasma is low and less than 1% of the concentration of L-proline, which ranges from 40 to 150 mmol/L plasma (Nagata et al, 1992;Bruckner and Hausch, 1993). D-proline is partly renally excreted in its unmetabolized form and effectively oxidized by D-amino-acid oxidase to a-keto-d-amino-valeric acid, which is further metabolized (Schieber et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, D-amino acids are synthesized in vivo by microorganisms by transformation of L-isomers, which are enzymatically catalyzed by amino-acid oxidases, transaminases and racemases (Friedman, 1999). The concentration of D-proline in the human plasma is low and less than 1% of the concentration of L-proline, which ranges from 40 to 150 mmol/L plasma (Nagata et al, 1992;Bruckner and Hausch, 1993). D-proline is partly renally excreted in its unmetabolized form and effectively oxidized by D-amino-acid oxidase to a-keto-d-amino-valeric acid, which is further metabolized (Schieber et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] and recently, it was reported that D-Ala has the relationship with various diseases in mammals. [16][17][18][19] Therefore, for the investigation of 44) and Boc-L-Cys 22,45,46) have been reported. Our method 22) using Boc-L-Cys is an improvement of the method reported by Hashimoto et al 46) The analytical conditions were examined using the cerebellum of a normal ddY/DAO ϩ mouse, the tissue having a high DAO activity, from which the amounts of the naturally occurring D-amino acids are small.…”
Section: Analytical Methods For the Determina-tion Of D-amino Acids Imentioning
confidence: 99%
“…[10][11][12][13][14][15] The D-alanine (D-Ala) amounts have also been reported to change in the case of diseases. [16][17][18][19] Though the D-amino acids are being noticed as the candidates of physiologically active substances, the determination of most Damino acids is difficult because their amounts in mammalian tissues are extremely low and various interfering substances are present in the tissues. In addition, their functions, origins and regulation mechanisms still remain unknown for the most part.…”
Section: Introductionmentioning
confidence: 99%
“…D-Alanine is the first D-amino acid found in serum of guinea pig and mice [16]. Subsequent studies demonstrated that free D-alanine is one of the D-amino acids naturally occurring in the mammalian tissues including brain and blood [17][18][19][20][21][22]. D-Alanine, like D-serine, is also a selective and potent agonist at the glycine-modulatory site on the NMDA receptors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%